2019
DOI: 10.1590/0101-60830000000182
|View full text |Cite
|
Sign up to set email alerts
|

Development of weCope, a mobile app for illness self-management in schizophrenia

Abstract: Objective: To describe the development of weCope, a Portuguese mobile app for people with schizophrenia. Methods: The development of weCope followed 4 stages: I-102 people with psychotic disorders completed an online questionnaire; II-a multidisciplinary focus group was conducted among five mental health professionals; III-we developed the app; IV-9 participants used weCope during 8 weeks to assess its efficiency. Results: weCope targets coping with voices, problem solving, goals setting and stress management,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 25 publications
1
5
0
4
Order By: Relevance
“…14 40 45 Others technologies allowed the contact with therapists in crisis situations. 37 This finding aligned with evidence in the literature that technologybased interventions can help people manage physical symptoms 47 and that interventions designed to increase self-efficacy to manage physical symptoms are effective in chronic-disease populations. 48 Only a few of the included technologies were created with the intent of aiding therapists and patients to jointly set rehabilitation goals.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…14 40 45 Others technologies allowed the contact with therapists in crisis situations. 37 This finding aligned with evidence in the literature that technologybased interventions can help people manage physical symptoms 47 and that interventions designed to increase self-efficacy to manage physical symptoms are effective in chronic-disease populations. 48 Only a few of the included technologies were created with the intent of aiding therapists and patients to jointly set rehabilitation goals.…”
Section: Discussionsupporting
confidence: 70%
“… 19 Another study indicated that older individuals had more difficulties using these technologies. 37 Users wanted their technology to be able to track goals, physical activity and other health measures, such as heart rate, weight and diet, 37 40 as well as have more specific and individualised relevant goals and personalised feedback from health professionals. 31 41 Devi et al conducted semistructured interviews with 16 participants to explore patient experiences of using a web-based cardiac rehabilitation programme.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…estudos. [10][11][12][13][15][16][17][18][19][20][21][22][23]25,27,28,[30][31][32][33][34][35][37][38][39]42,[44][45][46][47][48]50,52,54 Tendo foco no monitoramento do humor foi encontrado um total de cinco: um sobre a eficácia e outro sobre o desenvolvimento de App denominado MoodPrism; 17,22 um sobre o desenvolvimento do App G-MOJI 34 baseado no automonitoramento do humor por meio de emojis; um com foco na viabilidade de App para promover a SM positiva em adolescentes, chamado CopeSmart; 11 e um outro com foco no desenvolvimento de um App (sem nome) para jovens com Depressão Maior, 27 ideação suicida e autodano. O que se destaca nesse App é o potencial de fornecer graficamente mais evidências sobre a correlação entre o humor autoavaliado e as avaliações clínicas conduzidas por métodos de classificação escrita, tais como escalas.…”
Section: Resultados Resultados Resultados Resultadosunclassified
“…Research-developed apps for mental and physical health management for people with SMI have empirical evidence for their acceptability and effectiveness. Use of illness management apps for people with SMI, such as FOCUS and weCope, has shown reductions in psychotic and depressive symptoms, and improvements in general functioning; 13,14 people with SMI have shown high rates of engagement with WellWave, an app which promotes physical activity; 6 people with a first episode psychosis who used PRIME, a motivational enhancement app, for 3 months reported fewer depressive symptoms and increased self-efficacy. 15…”
mentioning
confidence: 99%